Broadband metamaterial absorber using multi-disk structure in the THz region - Nguyen, The An; Nguyen, Thu Minh; Vu, Duy Chien; Vu, Dinh Lam; Pham, Van Hai; Pham, Van Dien; Nguyen, Thi Thuy; Tran, Manh Cuong (Communications in Physics, 2025)
This study has conducted the design, simulation, and optimization of a multilayer disk structure which works in the THz regime. Through the process of combining various materials and adjusting the correlation parameters between them, the three-layer structure demonstrates a high absorption capability within the frequency range of 5.6-7.9 THz, with an average absorption rate of up to 95%. The analytical results regarding the distribution of electric and magnetic fields on the surface and the electrical equivalent circuit model of the material further elucidate the absorption principles of the structure. Particularly, this structure also demonstrates an advantage in its ability to function effectively when the angle of incidence is altered up to 45 degrees.